Kinetic Monte Carlo simulations of the growth of polymer crystals - Doye, J; Frenkel, D (1999)
Based upon kinetic Monte Carlo simulations of crystallization in a simple polymer model we present a new picture of the mechanism by which the thickness of lamellar polymer crystals is constrained to a value close to the minimum thermodynamically stable thickness, lmin. The free energetic costs of the polymer extending beyond the edges of the previous crystalline layer and of a stem being shorter than lmin provide upper and lower constraints on the length of stems in a new layer. Their combined effect is to cause the crystal thickness to converge dynamically to a value close to lmin where growth with constant thickness then occurs. This description contrasts with those given by the two dominant theoretical approaches. However, at small supercoolings the rounding of the crystal profile does inhibit growth as suggested in Sadler and Gilmer's entropic barrier model. © 1999 American Institute of Physics.